2019
DOI: 10.1371/journal.pone.0220344
|View full text |Cite
|
Sign up to set email alerts
|

Cecropin-like antimicrobial peptide protects mice from lethal E.coli infection

Abstract: Resistance of pathogenic bacteria to standard antibiotics is an issue of great concern, and new treatments for bacterial infections are needed. Antimicrobial peptides (AMPs) are small, cationic, and amphipathic molecules expressed by metazoans that kill pathogens. They are a key part of the innate immune system in both vertebrates and invertebrates. Due to their low toxicity and broad antimicrobial activities, there has been increasing attention to their therapeutic usage. Our previous research demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, some studies have shown the potential of these peptides in vivo. For example, single intraperitoneal administrations of H. cecropia Cecs A and B, and Danaus plexipibus DAN2 decreased mortality in acutely E. coli -infected rodent models [114,130]. In addition, mice subjected to DAN2 doses two-fold higher than their most effective antibacterial concentration did not display any behavioral or morphological abnormalities, demonstrating in vivo that these peptides lack toxic effects after acute treatments [130].…”
Section: Health Benefits Of Natural Cecs and Synthetic Cec-analogsmentioning
confidence: 99%
“…However, some studies have shown the potential of these peptides in vivo. For example, single intraperitoneal administrations of H. cecropia Cecs A and B, and Danaus plexipibus DAN2 decreased mortality in acutely E. coli -infected rodent models [114,130]. In addition, mice subjected to DAN2 doses two-fold higher than their most effective antibacterial concentration did not display any behavioral or morphological abnormalities, demonstrating in vivo that these peptides lack toxic effects after acute treatments [130].…”
Section: Health Benefits Of Natural Cecs and Synthetic Cec-analogsmentioning
confidence: 99%
“…Members of the cecropin family typically have peptide chains consisting of 31-39 amino acids and possess broad-spectrum antimicrobial activities (Brady et al, 2019). Several studies have shown that cecropin, when used as a feed additive, can increase the performance of livestock and poultry while also protecting them from lethal pathogen infections (Wen and He, 2012;Wu et al, 2012;Xiao et al, 2015;Shrestha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses using the ExPASy ProtParam [30] tool indicate that serrulin is, like other AMPs, a cationic molecule, containing a positive charge (+4) (Figure S3). Generally, cationic antimicrobial peptides act on the membrane of microorganisms by an electrostatic difference [31], but there are AMPs that act internally and can interact on ribosome, internal proteins, or nucleic acids (DNA or RNA) [32,33,34]. Like ctenidins and acanthoscurrins, the mechanism of action of serrulin was not identified in this work, so it is not possible to compare its characteristics with those of similar molecules.…”
Section: Resultsmentioning
confidence: 99%